2003
DOI: 10.1023/a:1020780022549
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: WRKY proteins are a recently identified class of DNA-binding proteins that recognize the TTGAC(C/T) W-box elements found in the promoters of a large number of plant defense-related genes. With oligo molecules containing the W-box sequences as probes, we detected a number of WRKY DNA-binding activities in Arabidopsis that were induced by salicylic acid (SA). Search of the Arabidopsis genome identifies 72 genes encoding proteins characteristic of WRKY DNA-binding transcription factors that can be divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
258
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 763 publications
(272 citation statements)
references
References 31 publications
12
258
0
2
Order By: Relevance
“…ChIP assays confirmed the association of WRKY with its own promoter and the cwp2 promoter (and also the cwp1 and myb2 promoters; see below for discussion). The expression of the plant wrky genes was induced in response to changing environments, including development, dormancy, biotic and abiotic stress, disease resistance, and senescence (30,32). We also found that the giardial WRKY localized exclusively to the two nuclei, and its expression increased significantly during encystation, suggesting that it may also play a role in this differentiation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…ChIP assays confirmed the association of WRKY with its own promoter and the cwp2 promoter (and also the cwp1 and myb2 promoters; see below for discussion). The expression of the plant wrky genes was induced in response to changing environments, including development, dormancy, biotic and abiotic stress, disease resistance, and senescence (30,32). We also found that the giardial WRKY localized exclusively to the two nuclei, and its expression increased significantly during encystation, suggesting that it may also play a role in this differentiation.…”
Section: Discussionmentioning
confidence: 56%
“…More than 70 members of the WRKY family found in Arabidopsis thaliana have diverse roles in response to various pathogen and environmental conditions (27). The mRNA levels of these wrky genes also increased in response to these changing environments (30,32). The wrky gene family has been found in many plants but has not been identified to date in yeast or animal genomes (33).…”
mentioning
confidence: 99%
“…A number of cis-acting elements such as WRKY binding sites (W boxes) with a TGAC core sequence were shown to be associated with genes involved in the plant defense response against pathogens Dong et al 2003;Xu et al 2006). For example, a W box elicitor response element in the promoter of the tobacco class I chitinase gene CHN50 is specifically bound by pathogen-induced TDBA12 and purified WRKY proteins (Yang et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the plasticity of plant response to water limited conditions is governed by a number of transcription factors (TFs) which can modulates and regulates various stress inducible genes either independently or constitutively. More than 50 different TFs have been identified and characterized, are found to be member of large multigene families such as bZIP-(Martinez-Garcia et al, 1998), MYB (Jin & Martin, 1999), MYC, AP2/ERF (Riechmann, & Meyerowitz., 1998) , NAC (Kikuchi et al, 2000) and WRKY (Dong et al, 2003). Many genes that respond to multiple stresses are induced by abscisic acid (ABA); a phytohormone which acts as a key signaling intermediate in controlling the expression of stress related genes.…”
Section: Transcript Profilingmentioning
confidence: 99%